2020
DOI: 10.21203/rs.3.rs-92169/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

EGFL6 Promotes Colorectal Cancer Cell Growth and Mobility and the Anti-cancer Property of Anti-EGFL6 Antibody

Abstract: BackgroundA reliable cancer biomarker will be critical for advanced colorectal cancer (CRC) therapeutic approaches since current treatments are limited to certain patient characteristics, such as age, sex, comorbidities and patients received self-expandable metal stents implantations. The association of epidermal growth factor-like domain 6 (EGFL6) with cancer development has been reported. Here, we focused on the role of EGFL6 in CRC progression and its clinical relevance. MethodsAn anti-EGFL6 antibody was ge… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Chronic kidney disease (CKD) is a common condition with various health consequences especially in children. Studies showed that patients with CKD had a higher risk of death and a higher risk of hospitalization compared with their non-CKD counterparts [1]. Thyroid disorders, which are prevalent in CKD patients, have been reported to be a risk factor for death [2].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic kidney disease (CKD) is a common condition with various health consequences especially in children. Studies showed that patients with CKD had a higher risk of death and a higher risk of hospitalization compared with their non-CKD counterparts [1]. Thyroid disorders, which are prevalent in CKD patients, have been reported to be a risk factor for death [2].…”
Section: Introductionmentioning
confidence: 99%